2016
DOI: 10.1016/j.scienta.2015.11.034
|View full text |Cite
|
Sign up to set email alerts
|

Reviewing current knowledge on olive (Olea europaea L.) adventitious root formation

Abstract: Olive (Olea europaea) is one of the most important fruit species in the Mediterranean basin, where 95% of the world's olive orchards are planted, and it has become an economically valuable crop worldwide, due to an increasing interest in olive oil for human consumption. New olive orchards are being planted outside the Mediterranean, calling for an effort to identify the genotypes best adapted to the new conditions. However, some olive cultivars remain difficult to propagate, which significantly reduces the cap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
45
0
8

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 53 publications
(56 citation statements)
references
References 302 publications
(369 reference statements)
3
45
0
8
Order By: Relevance
“…Interações microbiológicas que envolvem o crescimento e desenvolvimento são fundamentais em processos de formação das mudas de oliveira, podendo ser encontrado microrganismos como fungos micorrízicos arbusculares, que proporcionam um incremento no desenvolvimento das estacas já enraizadas, aumentando o sistema radicular, bem como a parte aérea das plantas (Ferreira et al, 2015), e também bactérias que promovem o crescimento das plantas por meio de polímeros e hormônios produzidos (Montero-Calasanz et al, 2013). No entanto, a maioria dos estudos envolvendo enraizamento ou crescimento de mudas de oliveira concentra-se em fatores químicos (Porfírio et al, 2016) e poucos são os trabalhos que consideram as interações microbiológicas, essenciais nas etapas iniciais de produção.…”
Section: Resultsunclassified
See 1 more Smart Citation
“…Interações microbiológicas que envolvem o crescimento e desenvolvimento são fundamentais em processos de formação das mudas de oliveira, podendo ser encontrado microrganismos como fungos micorrízicos arbusculares, que proporcionam um incremento no desenvolvimento das estacas já enraizadas, aumentando o sistema radicular, bem como a parte aérea das plantas (Ferreira et al, 2015), e também bactérias que promovem o crescimento das plantas por meio de polímeros e hormônios produzidos (Montero-Calasanz et al, 2013). No entanto, a maioria dos estudos envolvendo enraizamento ou crescimento de mudas de oliveira concentra-se em fatores químicos (Porfírio et al, 2016) e poucos são os trabalhos que consideram as interações microbiológicas, essenciais nas etapas iniciais de produção.…”
Section: Resultsunclassified
“…O método de propagação vegetativa mais utilizada na olivicultura é a estaquia devido, principalmente, a sua simplicidade e capacidade de formação de raízes adventícias pelas estacas (Porfírio et al, 2016). Diferentes cultivares de oliveira apresentam respostas distintas quanto ao enraizamento das estacas, sendo que a época do ano pode influenciar nesse processo, devido ao estado fenológico das plantas .…”
Section: Introductionunclassified
“…Among the factors that may influence adventitious rooting (reviewed in Porfirio et al, 2016a), oxidative enzymes and auxins are the most studied and discussed. The involvement of auxins in adventitious rooting has been studied for a long time (Wiesman et al, 1989) and they are extensively used in plant propagation protocols as root-inducing compounds (Preece, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…The two main natural auxins are indole-3-acetic acid (IAA) and indole-3-butyric acid (IBA), quantified by various methods, as recently revised by Porfirio et al (2016b). Evidence suggests that IAA possibly promotes adventitious rooting through a signaling network similar to that happening in lateral roots, involving auxin response factors (ARF) and other plant hormones (Porfirio et al, 2016a). On the other hand, IBA auxin activity seems to be a result of its conversion into IAA (Korasick et al, 2013) by peroxissomal enzymes Zolman et al, 2007Zolman et al, , 2008.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies suggested that the inhibition of adventitious root formation was related to the capacity of the tissue to initiate root primordia rather than to the presence of an anatomical barrier (Amissah, Paolillo, & Bassuk, ; Davies & Hartmann, ; White & Lovell, ). Thus far, 2D histological analyses have been applied to characterize the anatomical basis of poor rooting ability (Amissah et al, ; Ballester, San‐José, Vidal, Fernández‐Lorenzo, & Vieitez, ; Harbage, Stimart, & Evert, ; Porfírio, Gomes da Silva, Cabrita, Azadi, & Peixe, ). However, the intrinsic limitation of 2D serial sections, which provide only sporadic characterization of the tissue along the cutting base, has encumbered these attempts.…”
Section: Introductionmentioning
confidence: 99%